Human Papillomavirus Prevalence and Associated Factors in Indigenous Women in Ecuador: A Cross-Sectional Analytical Study - José Ortiz Segarra; Bernardo Vega Crespo; Alfredo Campoverde Cisneros; Katherine Salazar Torres; Dayanara Delgado López; Stalin Ortiz (MDPI AG, 2023)
Cervical cancer (CC) is the second leading cause of death from malignancy in women in Ecuador. Human papillomavirus (HPV) is the main causative agent of CC. Although several studies have been conducted on HPV detection in Ecuador, there are limited data on indigenous women. This cross-sectional study aimed to analyze the prevalence of HPV and associated factors in women from the indigenous communities of Quilloac, Saraguro and Sevilla Don Bosco. The study included 396 sexually active women belonging to the aforementioned ethnicities. A validated questionnaire was used to collect socio-demographic data, and real-time Polymerase Chain Reaction (PCR) tests were used to detect HPV and other sexually transmitted infections (STIs). These communities are located in the southern region of Ecuador and face geographical and cultural barriers to accessing health services. The results showed that 28.35% of women tested positive for both types of HPV, 23.48% for high-risk (HR) HPV, and 10.35% for low-risk (LR) HPV. Statistically significant associations were found between HR HPV and having more than three sexual partners (OR 1.99, CI 1.03-3.85) and Chlamydia trachomatis infection (OR 2.54, CI 1.08-5.99). This study suggests that HPV infection and other sexually transmitted pathogens are common among indigenous women, highlighting the need for control measures and timely diagnosis in this population.